AGENCY PROBLEM ANALYSIS FROM COMMITTEE AND OWNERSHIP STRUCTURES - Bayu Indra Setia; Erik Syawal Alghifari; Nugraha Nugraha; Maya Sari (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
This study aims to determine the factors that influence the agency problem. A sample of 14 restaurant, hotel, and tourism sub-sector companies listed on the Indonesia Stock Exchange during the 2010–2019 period with a total of 140 observations was used as the unit of analysis. The method used is descriptive and verified with panel data regression analysis. The results showed that the audit committee and independent commissioners had a positive and significant effect on agency problems, while managerial ownership and institutional ownership had a negative and significant effect on agency problems